Phenylethanoid Glycosides From Callicarpa kwangtungensis Chun Attenuate TNF-α-Induced Cell Damage by Inhibiting NF-κB Pathway and Enhancing Nrf2 Pathway in A549 Cells - Zheng, Jing-Na; Zhuo, Jian-Yi; Nie, Juan; Liu, Yan-Lu; Chen, Bao-Yi; Wu, Ai-Zhi; Li, Yu-Cui (Frontiers in Pharmacology, 2021)
Background: Acute lung injury (ALI) is a complicated and severe lung disease, which is often characterized by acute inflammation. Poliumoside (POL), acteoside (ACT) and forsythiaside B (FTB) are phenylethanoid glycosides (PGs) with strong antioxidant, anti-inflammatory, and anti-apoptotic properties, which are extracted from Callicarpa kwangtungensis Chun (CK). The aim of this study was to investigate the protective effects of POL, ACT, FTB against TNF-α-induced ALI cell model and explore their potential mechanisms. Methods and Results: MTT method was used to measure cell viability. Flow cytometry was used for detecting the apoptosis rate. Reactive oxygen species (ROS) activity was determined using fluorescence microscope. The effects of POL, ACT, FTB on the activities of nuclear factor erythroid-2 related factor 2 (Nrf2), nuclear factor kappa-B (NF-κB) and the expression of their downstream genes were assessed by western blotting and RT-PCR in A549 cells. In the current study, POL, ACT and FTB dose-dependently attenuated TNF-α-induced IL-1β, IL-6 and IL-8 productions, cell apoptosis, and ROS activity. POL, ACT, FTB not only increased in the mRNA levels of antioxidative enzymes NADPH quinone oxidoreductase (NQO1), glutamate cysteine ligase catalytic subunit (GCLC), heme oxygenase (HO-1), but also decreased the mRNA levels of IL-1β, IL-6 and IL-8. Furthermore, they upregulated the expression of Keap1 and enhanced the activation of Nrf2, while decreased the expressions of phosphor-IκBα (p-IκBα) and nuclear p65. In addition, no significant changes were observed in anti-inflammatory and antioxidant effects of POL, ACT, FTB following Nrf2 and NF-κB p65 knockdown. Conclusion: Our study revealed that POL, ACT, FTB alleviated oxidative damage and lung inflammation of TNF-α-induced ALI cell model through regulating the Nrf2 and NF-κB pathways.